Demographic Attributes of Knowledge, Attitude, Practices, and One Health Perspective Regarding Diarrhea in Pakistan - Abbasi, Ariba; Shahzad, Khuram; Shabbir, Rana Muhammad Kamran; Afzal, Muhammad Sohail; Zahid, Hamza; Zahid, Talha; Ahmed, Haroon; Cao, Jianping (Frontiers in Public Health, 2021)
Background: loose bowels is a clinical sign of gastrointestinal transport channel proteins, channels, physical and chemical boundaries being harmed, prompting issues of water and electrolyte transport in the intestinal system. It is still considered as a major reason of emergency visit to hospitals in low-middle income countries. Zinc is better treatment along with ORS for diarrhea. KAPs survey usually is conducted to collect information about general or specific topics of a particular population. The objective of the study was to investigate the knowledge, attitude, practices (KAP) and one health perspective regarding diarrhea among the participants from urban and rural population of Rawalpindi and Islamabad, Pakistan. Methods: Data was collected by conducting a survey among residents of twin cities over a period of 6 months (from July 2020 to December 2020). The questionnaire compromised of socio-demographic features and degree of KAP with respect to diarrhea management and control. One way ANOVA test were applied to observe the demographic relationship and various factors influencing knowledge, attitude, practices and one health perspective about diarrhea. Results: A total of 338 subjects participated in the study. Female subjects were in majority with 63% while rest were male. Majority of the participants were of age group between 15-25 years and 79.6% participants were un-married. Leading ethnic group was Punjabi with 52.7% and least were of Sindhi ethnicity with 8.6%. Age has significant association with respect to knowledge and attitude. Religion has significant association with respect to knowledge, practices and one health while education/qualification has association with knowledge. While rest of the variables found no association with each other. Conclusion: It is concluded from the recent study that most residents of twin cities of Pakistan knew about diarrhea and had a good attitude and practices toward it. Age, religion, and education has different role regarding different diseases in the population of Pakistan. The current study has its limitations as well. Some part of the study was conducted in the capital of Pakistan. It would be better to explore the remote areas of Pakistan where basic amenities of life such as literacy, poverty and unemployment are not available.